Sosialisasi Budidaya Hidroponik : Tanam Tanpa Tanah dan Menggunakan Barang Bekas untuk Masyarakat Desa Rumbio Kecamatan Kampar - Yanuar Al Fiqri; Fanni Rozana; Yulia Vioni Pasaribu; Mutiara Mutiara; Mauren Azzahra; Tiara Putri Afriani; Ayu Nabila Wardhani Siregar; Ahmad Ridho Ismail; Renaldi Renaldi; Rayhan Thoriq Ramadhan; Tengku Mahardika Bima Kurniawan (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Kukerta are activities in the form of community service which aim to foster a sense of mutual care for the community. Rumbio Village is a village located in Kampar District, Kampar Regency, Riau Province. One of the potentials found in this village is in the agricultural and food sectors. Therefore, based on the potential of this village, the Riau University Kukerta activity aims to provide education regarding land use for food security using hydroponic techniques. The existence of hydroponic and verticulture planting systems can increase income and can also be consumed daily with minimal expenditure. Apart from that, this activity aims to provide knowledge and skills to the people of Rumbio Village regarding the correct procedures for carrying out hydroponic techniques. The methods used in this activity are socialization of hydroponics using used goods, hydroponic demonstrations, discussions and questions and answers, as well as monitoring and evaluation. The results of the activity show that the socialization activities in Rumbio Village were carried out well and smoothly, which can be seen from the enthusiasm of the community in participating in hydroponic socialization activities from start to finish, as well as the growing motivation within the community to apply hydroponic techniques using used goods.